تحليل الهيكل المكاني للمراكز الحضرية في محافظة المثنى باستخدام الأساليب التخطيطية - عبدالله، ماهر ناصر (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2017)
تم التعرف من خلال هذه الدراسة على مشكلة اختلال التوازن في المراكز الحضرية لمحافظة المثني، وقد تبين أن هناك تركزا سكانيا عال في مدينة السماوة تبعتها مدينة الرميثة ثم الخضر، وتم فحص أمكانية وجود مدينة مهيمنة من خلال قانون المدينة الأولي لجيفرسون وقاعدة الرتبة والحجم لزيف ودليل الهيمنة، وتطبيق مؤشر التوازن الحضري لمعرفة حجم الاختلال التوازني في شبكة المدن الحضرية، واتضح من تحليل النتائج عدم انطباق قاعدة الرتبة والحجم ووجود ما يسمي المدينة المهيمنة (السماوة) نتيجة أسباب اقتصادية واجتماعية وإدارية ، ولغرض أيجاد في توزيع السكان فلابد من اتخاذ مجموعة من الإجراءات التي أوصى بها الباحث.
Through over the following study, it is identified that there is problem of imbalance equilibrium among the urban centers of Al- muthanna province. It shows that there is a high population concentration in Samawa, Rumaitha, Khudir cities respectively. Also, it checked the possibility of having a primate city throughout the law of the primate city of Jefferson, rank- size rule of Zepf, the law primate city, The Index of Primacy, and coefficient in measuring the extent of inequality in the distribution of urban cities. Throughout the results of the present study, it became clear that there is inconsistency between the rank- size rule and the existence of what is called the primate city "Samawa" because of some administrative, economical, and social reasons. In order to have balance equilibrium of population distribution, it is important to have in consideration the recommendations of the researcher.
Keywords: المثنى، العراق -- الجغرافيا البشرية -- التنمية الحضرية -- التخطيط العمراني